Pengaruh Inovasi Produk terhadap Kinerja Keuangan pada UMKM Minuman Kota Bandung - Dwi Siti Halijah; Epi Fitriah (Jurnal Riset Akuntansi, 2024)
Abstract. Product innovation is a crucial factor in modern business competition, significantly impacting organizational financial performance. This study examines the relationship between financial performance and product innovation in beverage industry SMEs in Bandung. Innovation is believed to enhance competitiveness, improve financial outcomes, and drive business growth. The study evaluates innovation quality through creativity, uniqueness, functionality, and added value. Its goal is to provide SMEs with guidance on leveraging innovation for financial growth and identifying the correlation between innovation efforts and financial success. The research addresses: (1) product innovation conditions, (2) financial performance, and (3) the impact of product innovation on financial performance. A quantitative approach using a survey-based verification method involved 80 respondents selected through convenience sampling. Data were analyzed using SmartPLS 3.0. The study found that product innovation in Bandung's beverage SMEs positively and effectively impacts financial performance. These findings emphasize the importance of product innovation for SME financial success. Abstrak. Inovasi produk adalah faktor penting dalam persaingan bisnis modern yang memengaruhi kinerja keuangan organisasi. Penelitian ini mengkaji hubungan antara kinerja keuangan dan inovasi produk pada UMKM industri minuman di Bandung. Inovasi diyakini meningkatkan daya saing, hasil keuangan, dan pertumbuhan bisnis. Penelitian mengevaluasi kualitas inovasi melalui kreativitas, keunikan, fungsionalitas, dan nilai tambah. Tujuannya memberikan panduan bagi UMKM dalam memanfaatkan inovasi untuk pertumbuhan keuangan serta mengidentifikasi korelasi antara inovasi dan kesuksesan finansial. Penelitian ini membahas: (1) kondisi inovasi produk, (2) kinerja keuangan, dan (3) pengaruh inovasi produk terhadap kinerja keuangan. Pendekatan kuantitatif berbasis survei dengan 80 responden dipilih melalui convenience sampling. Data dianalisis menggunakan SmartPLS 3.0. Penelitian menemukan inovasi produk di UMKM minuman Bandung berpengaruh positif pada kinerja keuangan, yang sangat efektif. Temuan ini menegaskan pentingnya inovasi produk untuk kesuksesan keuangan UMKM.